Durability of Northern Sarawak Shale against Short-Term Weathering Based on Geochemistry, Mineralogy, and Textural Properties - Anthony, Fianita (Curtin University, 2022)
The research aims to study the durability and short-term weathering of the Northern Sarawak shale. Various approaches have been adopted in the study, including durability assessment, physical properties, mineralogy, chemical composition, microtextural analysis, and mechanisms of weathering through a modified natural slake test. All the studied shales have low to very low durability. Distinct differences have been discussed clearly and comprehensively between the least durable and the most durable shale in the study area.